The Psychological Impacts of the Pamong Praja Police Unit as the Front Guard in Handling, Preventing, Spreading the Case of Covid-19 - Andjani Antonetha Peni; Indra Yohanes Kiling; Yeni Damayanti (Journal of Health and Behavioral Science, 2022)
Coronavirus Disease 2019 (Covid-19) is an infectious disease with a pandemic status globally and has spread throughout Indonesia, including NTT. Covid-19 cases in NTT in 2021 experienced an increase of 312 deaths. The NTT Provincial Civil Service Police Unit is part of the task force and the front guard handling Covid-19 in the NTT region. This research uses qualitative research with the Photo Elicitation data collection method on seven informants. The study found that in the initial conditions, the informants did not have adequate information about handling covid-19; therefore, they became a risk group for Covid-19 and experienced various obstacles. These things impacted their psychological conditions (anxiety, insomnia, and interpersonal conflict) and physiological. Meanwhile, informants are accustomed to handling Covid-19 to reduce the negative psychological impact of the current situation. Community cooperation with Satpol PP members is needed to reduce the number of Covid-19.